2015
DOI: 10.1139/cjce-2014-0496
|View full text |Cite
|
Sign up to set email alerts
|

Scenario shakemaps for Montreal

Abstract: Montreal has significant seismic risk due to the combination of moderate seismicity, high population density, and vulnerable infrastructure. An important tool in damage and risk assessment is a scenario shakemap, which shows the expected ground shaking intensity distribution patterns. In this study, we use regional ground motion and site response evaluations to generate scenario shakemaps for Montreal. The impact of event location on expected ground motions and intensities was tested by considering the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The method proposed in this paper integrates the data involving hazard and vulnerability analysis. The seismic hazard at the local scale is based on an existing soil microzonation [25,26,[28][29][30][31]. The vulnerability assessments for masonry buildings are based on the analyses performed by Lefebvre [32].…”
Section: Methods To Assess the Vulnerability Of The Hotel Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…The method proposed in this paper integrates the data involving hazard and vulnerability analysis. The seismic hazard at the local scale is based on an existing soil microzonation [25,26,[28][29][30][31]. The vulnerability assessments for masonry buildings are based on the analyses performed by Lefebvre [32].…”
Section: Methods To Assess the Vulnerability Of The Hotel Sectormentioning
confidence: 99%
“…Except for the 1732 M5.8 earthquake, which destroyed approximately 300 houses, the Montreal area has been affected by relatively weak events. However, recent estimates of seismic hazard and risk studies have shown that Modified Mercalli Intensities (MMIs) of VII and VIII events can be expected in the future [28]. On average, extensive and complete damage could affect approximately 0.5% of the total building stock and cause casualties (fatalities plus injuries) varying between 350 and 500 depending on the time of the earthquake occurrence [29].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of seismic risk, Montreal ranks as the second-highest city in Canada after Vancouver due to its seismicity and high population density. [25][26][27] Therefore, prioritizing earthquake loss assessment of residential buildings is vital. As illustrated in Figure 1, the circular chart presents the percentage of residential units in Montreal, categorized by building types.…”
Section: Introductionmentioning
confidence: 99%
“…Eastern Canada is a seismic‐prone region and comprises large cities, including Montreal, Ottawa, and Quebec City. In terms of seismic risk, Montreal ranks as the second‐highest city in Canada after Vancouver due to its seismicity and high population density 25–27 . Therefore, prioritizing earthquake loss assessment of residential buildings is vital.…”
Section: Introductionmentioning
confidence: 99%
“…The microzonation map is derived by combining information from seismic measurements and borehole data (Rosset, Bour, & Chouinard, 2015). The maps have been used to obtain Shakemap scenarios (Ghofrani, Atkinson, Chouinard, Rosset, & Tiampo, 2015) but has never been validated since no significantly large and close earthquake occurred in recent times and also because the seismic network in this region is very limited in number and quality of stations.…”
Section: Introductionmentioning
confidence: 99%